Estimation of mangrove carbon stocks from remote sensing and field survey-based data in Nghe An province - Nguyen Khac Manh; Nguyen Hai Hoa; Ngo Van Thanh Anh Tri; Nguyen Huu Quang Vinh; Nguyen Ngoc Linh; Nguyen Thu Thuy; Vu Van Truong; Nguyen Viet Duong; Nguyen Thi Hai Van (Journal of Forestry Science and Technology, 2025)
Mangrove forests mainly grow in tropical and subtropical regions, including Southeast Asia, coastal Africa, Latin America, and parts of Australia, which provide critical ecosystem services, including coastal protection from storms, shoreline stabilization, and carbon sequestration. This study determined the locations of mangrove cover, then estimated the biomass and carbon stocks of mangrove forests in Nghe An by integrating multi-source satellite imageries and field measurements. Sentinel-2A and PlanetScope multispectral images were used in combination with field inventory to characterize mangrove structures and their extent. The findings revealed that the total of AGB and BGB of mangrove forest was estimated at 109,824 tons and 31,849 tons, while the total of AGC and BGC of mangrove forests was calculated at 51,617 tons and 14,967 tons in 2025 by Sentinel-2, respectively. The total of ACS across the surveyed area sums up to 51,998 tons in 2025. The study highlights the need for nature-based solutions to mitigate climate change, including Carbon Payment for Forest Environmental Services (C-PFES), Reducing Emissions from Deforestation and Forest Degradation (REDD+). Besides fighting back climate changes, these approaches can also create financial incentives for local stakeholders to maintain and restore mangrove forests. Furthermore, it is essential to strengthen existing policies as well as revise policy frameworks that recognize the ecological and economic values of mangrove in Nghe An province.